Solving bimatrix games with fuzzy payoffs by introducing Nature as a third player - Larbani, Moussa (Elsevier, 2009)
The paper elaborates on the fuzzy bimatrix games. The payoffs are assumed to be fuzzy intervals with bounded support as defined by Dubois and Prade. A new equilibrium concept is defined for this game by introducing‘Nature’ as a third player and using-cuts. Sufficient conditions for its existence and a procedure for its computation are provided.